The movie musical! - Basinger, Jeanine (Alfred A. Knopf, 2019)
Leading film historian Jeanine Basinger reveals, with her trademark wit and zest, the whole story of the Hollywood musical--in the most telling, most incisive, most detailed, most gorgeously illustrated book of her long and remarkable career. From Fred Astaire, whom she adores, to La La Land, which she deplores, Basinger examines a dazzling array of stars, strategies, talents, and innovations in the history of musical cinema. Whether analyzing a classic Gene Kelly routine, relishing a Nelson-Jeanette operetta, or touting a dynamic hip hop number (in the underrated Idlewild), she is a canny and charismatic guide to the many ways that song and dance have been seen--and heard--on film. With extensive portraits of everyone from Al Jolson, the Jazz Singer; to Doris Day, whose iconic sunniness has overshadowed her dramatic talents; from Deanna Durbin, that lovable teen-star of the '30s and '40s; to Shirley T. and Judy G.; from Bing to Frank to Elvis; from Ann Miller to Ann-Margret; from Disney to Chicago . . . focusing on many beloved, iconic films (Top Hat; Singin' in the Rain; Meet Me in St. Louis; The Sound of Music) as well as unduly obscure gems (Eddie Cantor's Whoopee!; Murder at the Vanities; Sun Valley Serenade; One from the Heart), this book is astute, informative, and pure pleasure to read.